TANTANGAN PROFESIONALISME GURU DALAM PEMBELAJARAN ONLINE SELAMA PANDEMI - Moh Syamsi (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2021)
This pandemic is a challenge in developing creativity to the use of technology, not only the transmission of knowledge, but also how to ensure learning is delivered properly, the professionalism of teachers is required to be more than just the delivery of materials but also how to make effective and efficient classes in the online learning period. This article is the result of research that has been conducted of theachers in Schools at Glagah district of Lamongan Regency. This research uses qualitative research methods with a case study approach, data collection through interviews and observations which are then carried out descriptively constructive analysis. It becomes important the strategies used by teachers in making learning more fun and not burdensome for students and accompanying parents. The right strategy without reducing the quality of existing learning is to manage the best time, master the required technological devices, be fun but relaxed, and maintain good communication with the parents of learners.